2009
DOI: 10.1016/j.taap.2009.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Expression of kidney injury molecule-1 (Kim-1) in relation to necrosis and apoptosis during the early stages of Cd-induced proximal tubule injury

Abstract: Cadmium (Cd) is a nephrotoxic industrial and environmental pollutant that causes a generalized dysfunction of the proximal tubule. Kim-1 is a transmembrane glycoprotein that is normally not detectable in non-injured kidney, but is up-regulated and shed into the urine during the early stages of Cd-induced proximal tubule injury. The objective of the present study was to examine the relationship between the Cd-induced increase in Kim-1 expression and the onset of necrotic and apoptotic cell death in the proximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 47 publications
6
94
0
Order By: Relevance
“…In another study, Aoyagi et al (2003) noted an increase in the number of apoptotic cells in the renal cortex of cadmium-treated rats after 4 and 5 weeks of exposure, but that the level of apoptotic labeling was much less pronounced after 6 and 8 weeks of exposure. In more recent studies from our laboratory (Prozialeck et al, 2009a), we also found that cadmium caused a low level of apoptosis in the proximal tubules of subchronically exposed rats. However, the onset of apoptosis appeared to occur after Kim-1-dependent tissue repair processes had already been activated, suggesting that cadmium can produce significant changes in the cells before the onset of apoptosis.…”
Section: Role Of Necrosis Apoptosis and Autophagy In Cadmium Nephrosupporting
confidence: 59%
See 2 more Smart Citations
“…In another study, Aoyagi et al (2003) noted an increase in the number of apoptotic cells in the renal cortex of cadmium-treated rats after 4 and 5 weeks of exposure, but that the level of apoptotic labeling was much less pronounced after 6 and 8 weeks of exposure. In more recent studies from our laboratory (Prozialeck et al, 2009a), we also found that cadmium caused a low level of apoptosis in the proximal tubules of subchronically exposed rats. However, the onset of apoptosis appeared to occur after Kim-1-dependent tissue repair processes had already been activated, suggesting that cadmium can produce significant changes in the cells before the onset of apoptosis.…”
Section: Role Of Necrosis Apoptosis and Autophagy In Cadmium Nephrosupporting
confidence: 59%
“…However, it is less clear whether this mechanism can explain the actions of cadmium on N-cadherin in the proximal tubule, where the epithelial cells would be exposed to unknown concentrations of cadmium in the form of cadmium-protein or cadmium-thiol conjugates (Bridges and Zalups, 2005). Results of our own in vivo mechanistic studies to date have shown that at the time the initial cadmiuminduced changes in N-cadherin localization and Kim-1 expression are occurring, there is no evidence of necrosis, and only minimal evidence of oxidative stress or apoptosis in the proximal tubule (Prozialeck et al, 2003(Prozialeck et al, , 2009aProzialeck and Edwards, 2010). Again, these findings strongly suggest that cadmium may exert relatively specific effects on one of the many signaling pathways that regulate cadherin-mediated cell-cell adhesion in the proximal tubule.…”
Section: Cadmium and Cellular Signaling Cascadesmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6) Apoptosis disorders induce a disruption of tissue homeostasis and functions and are associated with many diseases, such as cancer, neurodegenerative disease and toxin-induced disease. 7) Cadmium can induce apoptosis in various tissues and cultured cells, including mouse liver, 8) rat kidney and testis, [9][10][11][12][13] human T cell line (CEM-C12 cells), lymphoma U937 cells, normal hepatocytes, liver L-02 cells, fetal lung fibroblast MRC-5 cells and prostate epithelial cells, [14][15][16][17][18][19] mouse mesangial cells, 20) rat lung epithelial cells, cortical neurons and renal tubular epithelial cells, [21][22][23] and porcine kidney LLC-PK 1 cells. 24) These observations indicate that cell death of the proximal tubule cells in the kidney through apoptotic pathways is one of the key events in cadmium-induced renal toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In another prospective study on 201 hospital patients with AKI, an increase of urinary KIM-1 was associated with increased mortality or dialysis requirement [44]. Its potential use as an early marker is based so far on limited data: a rise in its urinary levels was detectable before the increase of BUN and creatinine in plasma during cadmium-induced renal damage [64] as well as its expression in biopsy sections of kidney allograft recipients before histological signs of acute tubular necrosis became evident [99].…”
Section: Diagnostic Evidencementioning
confidence: 99%